The religious painting of Pia Górska - Anna Sieradzka (Sacrum et Decorum, 2014)
The religious painting of Pia Górska, a Polish artist active in the 1920s and 1930s, is sparsely preserved and little known. Her most outstanding works include two images painted in 1938-1939: Holy Virgin of Loreto (Patron Saint of Aviators) at the Church of St Francis of Assisi near the Warsaw airport of Okęcie and St Jude Thaddaeus in the Church of the Holy Cross in Warsaw. The paintings are characterized by their original treatment of iconography, which combines the dictates of tradition with the artist’s lyrical realism.